2023
DOI: 10.1136/bmjopen-2022-062149
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of duration of birth interval on adverse pregnancy outcomes in sub-Saharan Africa: a propensity score-matched analysis

Abstract: ObjectivesUnlike high-income countries, sub-Saharan African countries have the highest burden of adverse pregnancy outcomes such as abortion, stillbirth, low birth weight and preterm births. The WHO set optimal birth spacing as a key strategy to improve pregnancy outcomes. Estimating the impact of short and long birth intervals on adverse pregnancy outcomes based on an observational study like the Demographic and Health Survey (DHS) is prone to selection bias. Therefore, we used the propensity score-matched (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Proper timing and spacing of pregnancies is associated with a 25% reduction in mortality risk in children under-five years of age, that corresponds to an annual reduction of 1,836,000 deaths [ 2 ]. Conversely, a shorter interval between births has been linked with poor pregnancy and child health outcomes such as abortion and stillbirth, early neonatal and childhood deaths [ 2 – 9 ], preterm births, low birth weight [ 2 , 5 , 6 , 8 , 9 ], abnormal fetal position and presentation, low APGAR score, and respiratory distress syndrome [ 6 , 8 ]. Furthermore, studies have shown that children born after a shorter preceding birth intervals are more likely to suffer from malnutrition (stunting, underweight, and anemia) [ 2 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proper timing and spacing of pregnancies is associated with a 25% reduction in mortality risk in children under-five years of age, that corresponds to an annual reduction of 1,836,000 deaths [ 2 ]. Conversely, a shorter interval between births has been linked with poor pregnancy and child health outcomes such as abortion and stillbirth, early neonatal and childhood deaths [ 2 – 9 ], preterm births, low birth weight [ 2 , 5 , 6 , 8 , 9 ], abnormal fetal position and presentation, low APGAR score, and respiratory distress syndrome [ 6 , 8 ]. Furthermore, studies have shown that children born after a shorter preceding birth intervals are more likely to suffer from malnutrition (stunting, underweight, and anemia) [ 2 , 6 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a lack of data on the global estimate of short birth interval, the available evidence suggests that the prevalence varies between and within countries and regions. For example, in sub-Saharan African countries, the reported prevalence of short birth interval ranges from 22-60%, with a pooled prevalence of 46.9% [18]. In Central Asia, about 33% of births were reported to have occurred within a short interval.…”
mentioning
confidence: 99%